A comparative analysis of physical and tactical variables with play positions in final match FIFA World Cup 2014 - Bediri, S. M. (International Journal of Sports Science, 2016)
The final match of fifa world cup 2014 were analysis with the aim of this study which was to identify the difference between physical and tactical variables with play positions for national soccer teams in final match. The analysis was based on final match fifa world cup 2014 played between Germany and Argentina. Four physical and tactical variables were studies each one included group of variables. They were: distance covered (meters) - total distance covered, distance covered with and without possession of ball; time spent - in opposing half, in attaching third and in penalty area; speed - sprints and top speed; activity time spent- low, medium and high. Result analysis of this match revealed the following: (a) the most discriminate analysis related to defender players were distance covered- total distance covered, distance covered and distance covered with possession of ball; time spent- in opposing half, (b) the most discriminate analysis related to midfielder players were distance covered without possession of ball, (c) the most discriminate analysis related to forward players were time spent- in opposing half, in attaching third and in penalty area.